Material Anchors and Semiotics Agentive as tools for Navigation and Sense Generation in Geographic Space (Papeles, 2016)
This article attempts to make a thoughtful contribution from cognitive semiotics to human geography, more specifically to the processes of generation and navigationsense of subjects within the city. Navigating the geographical area of the city, means that subjects perform complex processes of conceptual integration networks anchored materially and cognitively with the geographical environment where thegeneration of sense and local action occur in an enactive way, this in order to establish a series of displacements with specific purposes and with the mediation of some artifacts that enable knowledge-based economy to the giving of sense. A contributionwill be made from anchor materials-distribution processes of cognition raised by Hutchins (1995, 2005) and the agentive semiotics of Niño (2015); which pose challenges to understand the geographic space and its generation of sense.
Keywords: anchors materials; anchors; agent; agenda